(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In contemporary higher education, language courses can no longer be treated as auxiliary subjects whose task is limited to correcting grammar or preserving literary norms. Their broader mission is to prepare students for meaningful participation in the communicative life of a discipline, where knowledge is produced, negotiated, defended, and transmitted through specialized forms of speech. This article examines the role of the Uzbek language course in shaping students’ disciplinary speech competence in higher education. Disciplinary speech competence is understood here as the integrated ability to comprehend, interpret, and produce subject-specific oral and written discourse in accordance with the conceptual vocabulary, genre conventions, communicative situations, and professional ethics of a field. Using an analytical qualitative design based on document analysis, comparative interpretation, and synthesis of pedagogical and linguistic scholarship, the article argues that the Uzbek language course occupies a structurally important position in this process because it connects general linguistic education with academic literacy, terminological precision, professional communication, and identity formation. The study shows that the educational value of the course increases when it is organized not around abstract language drills but around disciplinary texts, communicative tasks, genre models, terminology work, dialogic interaction, and reflective writing. The findings suggest that the Uzbek language course should function as a platform where students learn to formulate definitions, explain procedures, write reports, argue from evidence, participate in field-specific discussion, and adapt their speech to academic and professional contexts. Such an approach strengthens not only language proficiency, but also cognitive independence, communicative confidence, and the social accessibility of higher education in the state language.